Characterisation of Trichoderma spp. and assessment as biocontrol using dual culture assay against fungi associated with black pepper (Piper nigrum L.) diseases in Sarawak - Wilson, Joy Franco; Aman Zuki, Ameyra; Yee, Min Kwan (UNIMAS Publisher, 2022)
Black pepper (Piper nigrum L.) is one of the most widely used spices in food, beverage, cosmetics, and medicine. Black pepper production has suffered from various fungal diseases. Microbial biological control is an essential part of integrated disease management to reduce the heavy reliance on chemical fungicides. Trichoderma fungi comprise a large group of rhizocompetent filamentous fungi widely used in the biocontrol of plant pathogens. Three field surveys conducted on five black pepper farms in Belaga, Sarawak, identified three fungal diseases: yellowing, black berry, and foot rot. Based on the morphological and molecular characterisation, the identified fungal causal agents were Fusarium solani (yellowing disease), Colletotrichum gloeosporioides (black berry disease), and Phytophthora palmivora (foot rot disease). Twenty isolates of Trichoderma spp. were isolated from secondary forest and Biopark in Bintulu, Sarawak. Trichoderma isolates were characterised based on the morphological characteristics and molecular phylogenetic analysis using the rDNA internal transcribed spacer (ITS) region. Trichoderma isolates were separated into five distinct species, namely T. harzianum, T. virens, T. brevicompactum, T. tawa, and telomorphic Hypocrea lixii. Among the Trichoderma fungi, T. harzianum was the most frequently (65%) isolated species. Trichoderma harzianum (Isolates of TJ9, 10, and 16) showed antagonistic and inhibitory effects by 61 to 70% on in vitro mycelial growth against three common fungal pathogens of black pepper, P. palmivora, C. gloeosporioides, and F. solani. This study highlights the potential of using native Trichoderma fungi as biocontrol agents in the black pepper integrated disease management program.